Increased left ventricular stiffness assessed by diastolic wall strain causes symptoms in patients with premature ventricular contraction. (25th November 2020) - Fukuhara, E; Mine, T; Kishima, H; Ishihara, M
Abstract: Background: Premature ventricular contraction (PVC) is one of common arrhythmias and only some patients complain of PVC-related symptoms, however the mechanisms which cause the symptoms remain unclear in patients with PVCs. Purpose: We investigated whether the left ventricular (LV) stiffness assessed by diastolic wall strain (DWS) relate symptoms or not in patients with PVC. Methods: We studied 109 patients (48 males, age 60±19) with frequent monomorphic PVCs who underwent 12-leads electrocardiogram (ECG), signal-averaged electrocardiogram (SAECG), 24h-Holter ECG recording, and transthoracic echocardiography (TTE). Patients with structural heart disease or other arrhythmias such as atrial fibrillation were excluded. Clinical factors, blood samples for atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), and filtered QRS duration (f-QRS) and root mean square voltage of the terminal 40ms of the QRS complex (RMS40) obtained by SAECG were evaluated. We assessed PVC-SV (stroke volume during PVC), PVC-CI (CI between the previous sinus beat and VPC), and left ventricular (LV) stiffness assessed by diastolic wall strain (DWS). DWS was calculated from the M-mode echocardiographic measurement of the LV posterior wall thickness at end-systole (PWs) and end-diastole (PWd) during sinus rhythm, and DWS was defined as (PWs − PWd)/PWs. Results: 31patients (28%) had PVC-related symptoms (18 palpitation and 13 pulse deficit). Patients with PVC-related symptoms showed shorter PVC coupling interval index (52±10 vs. 58±11%, p=0.0140), reduced PVC-SV (21±12 vs. 29±17ml, p=0.0103) and decreased DWS (0.38±0.06 vs. 0.42±0.06, p=0.0011). Meanwhile, the level of BNP and ANP, f-QRS, RMS40, QRS morphology of PVC and the total number of PVC per day were not associated with PVC-related symptoms. On multivariate analysis, decreased DWS was only independently associated with PVC-related symptoms (p=0.0357, OR 2.3629 for each 0.1 decrease in DWS 95% CI 1.0583–5.5815). Conclusion: The reduced diastolic wall strain relates with PVC-related symptoms. The increased left ventricular stiffness might cause symptoms in patients with PVC. Funding Acknowledgement: Type of funding source: None